1999
DOI: 10.1007/s004649901118
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of unretrieved gallstones in the peritoneal cavity during laparoscopic cholecystectomy

Abstract: In most patients, unretrieved gallstones are of no consequence, but complications occur occasionally. It is therefore advisable to retrieve as many gallstones as possible during LC short of converting to a laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
1
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 55 publications
(23 reference statements)
2
125
1
6
Order By: Relevance
“…The incidence of spilt gallstones was noted to be 18.91 % in our series. In the literature the incidence ranges between 2 and 11 % [5]. The reason for our incidence being higher is likely to be the policy of taking on all gallbladder disease irrespective of the state of acuteness and friability of the gallbladder.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The incidence of spilt gallstones was noted to be 18.91 % in our series. In the literature the incidence ranges between 2 and 11 % [5]. The reason for our incidence being higher is likely to be the policy of taking on all gallbladder disease irrespective of the state of acuteness and friability of the gallbladder.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it makes a significant problem. The variety of complications caused by lost gallstones [3][4][5] may range from simple surgical site infection to more serious forms like broncholithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of lost stones have been reported in up to 40% of LC, 32 but only about 0.08% develop stone-related clinical problems, 33 which include intraperitoneal abscess, cutaneous umbilical sinus, systemic infection, fibrosis, adhesions, fistulas and migration to other sides. [32][33][34][35][36][37][38] We had no problems with the 3.3% missed stones. In OC, it is less of a problem because they can be retrieved more easily.…”
Section: Discussionmentioning
confidence: 99%
“…10,34,37 A large survey from the UK reported that only 17.9% of 396 surgeons who performed LC found it mandatory to retrieve split stones. 39 Certain steps are suggested if perforation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Cholelithoptysis is a rare complication, including chest discomfort and pleural effusion. 7 Some unusual late presentations of spilled gallstones and bile include abdominal wall sinus, 8 acute appendicitis, 9 and spontaneous erosion through the back, 10 Sometimes, chronic pain and jaundice can be seen from the retained stones. 11 Bile and stones should be completely removed from the peritoneal cavity, to prevent late complications and unwanted laparotomy.…”
Section: Methodsmentioning
confidence: 99%